Theology and the DC Universe - Mckee, Gabriel; Abraham, Roshan (Lexington Books, 2023)
Superman’s first appearance in Action Comics #1 (1938) proclaimed that the character would “reshape the destiny of the world.” The advent of the first superhero initiated a shared narrative—the DC superhero universe—that has been evolving in depth and complexity for more than 80 years. Superman, Batman, and Wonder Woman have become key threads in the tapestry of the American mythos, shaping the way we think about life, right and wrong, and our relationship with our own universe. Their narrative world is enriched by compelling stories featuring lesser-known characters like Dr. Fate, the Doom Patrol, John Constantine, and the Legion of Super-Heroes. Stories set within this shared universe have explored questions of death, rebirth, the apocalypse, the nature of evil, the origins of the universe, and the destiny of humankind. This volume brings together the work of scholars from a range of backgrounds who explore the role of theology and religion in the comics, films, and television series set in the DC Universe. The thoughtful and incisive contributions to this collection will appeal to scholars and fans alike.